Christopher French papers - French, Christopher, active 18th century
Three journals (1756-1764 and 1776-1778) kept by French while serving with the British Army in America. The first segment covers his service during the French and Indian War, especially during the siege of Louisbourg. Includes descriptions of New York City, Philadelphia, Princeton, Trenton, and Albany, as well as accounts of journeys through Canada and a trip to South Carolina during which conferences with various Indian tribes were held. The rest of the journal covers French's service during the American Revolution, especially his imprisonment in Hartford, Conn., and his duties in Rhode Island and New York. Individuals represented in the journal include John Burgoyne, William Howe, Jonathan Trumbull, and George Washington.
Microfilm edition available
Microfilm produced from originals in the Manuscript Division.
British army officer.
Collection material in English.
Keywords: Burgoyne, John, -- 1722-1792.; Howe, William Howe, -- Viscount, -- 1729-1814.; Trumbull, Jonathan, -- 1710-1785.; Washington, George, -- 1732-1799.; Great Britain. -- Army -- History; Indians of North America -- History -- Colonial period, ca. 1600-1775.; Albany (N.Y.) -- Description and travel; Canada -- History -- To 1763 (New France); Connecticut -- History -- Revolution, 1775-1783.; Hartford (Conn.) -- History; Louisbourg (N.S.) -- History; New York (N.Y.) -- Description and travel; New York (State) -- History; Nova Scotia -- History -- To 1763.; Philadelphia (Pa.) -- Description and travel; Princeton (N.J.) -- Description and travel; Rhode Island -- History -- Revolution, 1775-1783.; Trenton (N.J.) -- Description and travel; South Carolina -- History -- Colonial period, ca. 1600-1775.; United States -- History -- French and Indian War, 1754-1763.; United States -- History -- Revolution, 1775-1783 -- Campaigns; United States -- History -- Revolution, 1775-1783 -- Prisoners and prisons; Army officers, British